Household-level investments as accelerators of urban housing crises. Significance and motivation of private investors in housing markets outside the metropolises using the example of Salzburg - Van-Hametner, Andreas (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
So far, the increased emergence of financial investments on the housing markets has mainly been examined in metropolises or on a national level. Research focused primarily on institutional actors. The investigation of financial investments in housing space in cities below the metropolitan level and by individuals has so far been neglected. In the present study, I therefore focus on the manifestation of financial investments of private investors in housing markets outside the metropolises using a mixed-method approach of quantitative land register and data analysis as well as qualitative expert interviews. The paper shows that apart from the metropolises, the utilization of housing into an investment object is mainly carried out by private actors. They invest less out of speculation and in the expectation of an increase in value, but rather for private retirement or family provision and, above all, to secure value. This form of investment in housing also leads to serious consequences for other market players. The entire housing market is gradually focusing on this new type of investor. Real estate has therefore increasingly become a form of investment for many.